Improvement in the diagnostics of iron deficiency anemia using multiple marker combinations - Eun, Suk Yang; Yu, Seop Kim; Chan, Young Park; Jong, Dae Kim; Hye, Jeong Song (Universiti Kebangsaan Malaysia, 2015)
Anemia of chronic disease (ACD) frequently occurred in patients with chronic inflammatory diseases and can be treated by treating the underlying disease. On the other hand, iron-deficiency anemia (IDA), the most common type of anemia, occurred with iron loss or when the iron requirement of the body was increased. Since the treatment methods for ACD and IDA differ, it is important to clinically distinguish between the two types of anemia. In this study, we investigated and evaluated the performance of a number of biomarkers, including ferritin, soluble transferrin receptor (sTfR), hepcidin, C-reactive protein (CRP) and combination markers containing ferritin for the diagnosis of IDA using serum samples from Korean patients (80 ACD and 48 IDA Korean patients). Among the single markers, ferritin exhibited the best performance with 98.58% AUC and 97.50% sensitivity. In this study, a combination of two biomarkers was used to differentially diagnose IDA and ACD. Among the combination markers, ferritin + sTfR showed the best performance with 99.51% AUC and 98.75% sensitivity. We found that the ferritin + sTfR combination showed the best diagnostic performance with 1.25% higher SN than ferritin alone. Moreover, it also showed 10% better diagnostic performance than the single ferritin marker within the data range where the distinction between ACD and IDA is unclear. We propose that using combination markers containing ferritin may diagnose IDA more accurately and facilitate the determination of the appropriate anemia treatment to expedite patient recovery.